Integration of Imam Az-Zarnuji’s Educational Principles in Strengthening the Growth Mindset of Santri at Madrasah Diniyah Putri TBS Kudus - Ni'matul Maula; Taufikin Taufikin; Muhammad Rikza Muqtada; Muhammed Shamwil (Universitas Muhammadiyah Mataram, 2025)
This study explores the integration of Imam Az-Zarnuji’s educational principles from Ta’lim al-Muta’allim in shaping the growth mindset of female students at Madrasah Diniyah Putri TBS Kudus. Specifically, it investigates how key principles such as sincere intention (niyyah), respect for teachers, patience, perseverance, and discipline contribute to fostering a growth mindset characterized by resilience, openness to failure, and continuous self-improvement. Employing a qualitative descriptive design, data were collected through in-depth interviews, direct observations, and document analysis involving two teachers and fifteen students. Thematic analysis was used to identify patterns related to the application of Az-Zarnuji’s principles in students’ learning behavior and mindset development. The findings reveal that these classical Islamic educational values significantly reinforce modern psychological traits associated with the growth mindset, such as perseverance in learning, intrinsic motivation, and receptivity to feedback. The study offers concrete implications for Islamic education practice by demonstrating how integrating traditional pedagogical ethics with contemporary mindset theory can enhance students’ character formation and academic resilience. This integrative model presents a contextualized, holistic approach to developing growth-oriented learners in madrasah settings.